Range pole with integrated power system - HANKINS; CHRISTOPHER; MONSEF; ERIC (1999)
A range pole and in-line detachable battery module assembly including a range pole (10) with an elongated tubular graphite-epoxy range pole shell (102) which has a female cap assembly (108) and a male cap assembly (26) at opposite ends. The male cap assembly (26) includes a central bore (30) formed therethrough for containing an insulator plug (32) to which are attached coaxial electrical contacts (132, 134). The coaxial electrical contacts include a first contact surface surrounded by a second concentric contact surface. The male cap assembly includes an externally threaded stud (28) having a central bore (30) formed therethrough for containing an insulator plug (32) to which are attached pin sockets (67, 68) which contain spring-loaded male pin electrical contacts (34, 36). A detachable battery module (12) includes a tubular battery-module shell (24) which has a male cap (26) at one end. The male cap assembly also includes an externally threaded portion having a central bore formed therein for containing an insulator plug to which are attached sockets which contain spring-loaded male pin electrical contacts. A detachable tip (14) includes a ribbed aluminum tip body (150) having external ribs (152) formed in the sides thereof and a stainless steel tip (160). To assemble the battery module (12) to the range pole (10), the male cap assembly (26) of the battery module is threadedly joined to the female cap assembly (108) to cause pin contacts (34, 36) to become engaged to coaxial contacts (132, 134). The male cap assembly (26) at the other end of the range pole (10) is to be used for connection to other equipment.